Sustainability in Construction Project Delivery: A Study of Experienced Project Managers in Nigeria. Issue 6 (December 2016) - Zuofa, Tarila; Ochieng, Edward
Accomplishing sustainability-related targets in construction projects is progressively becoming popular. While some stakeholders generally recognize it as important, there are others with differing opinions. This article reports the results of an exploratory study involving interviews with 25 senior project managers from the construction industry who are involved in sustainability in some way. The main findings suggest that holistic sustainability practices and initiatives during the life cycles of projects in the construction industry have not been fully embraced. Although all interviews were carried out in Nigeria, the results may be applicable or interesting to other countries as well.